Implementasi Sidik Jari sebagai Otentikasi Parkir Kendaraan Menggunakan Raspberry Pi - Mohamad Dimyati Ayatullah; Devit Suwardiyanto; I Wayan Suardinata (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
Authentication of vehicle in and out of the parking lot is one of the problems that still need to be explored. Most parking lot authenticate the vehicle by record the number plate on the parking card. Officer verify the number plate on parking card with the vehicle registration certificate. This method requires accuracy of the parking attendant. Research carried out utilizing the vehicle driver's fingerprint identification and the introduction of vehicle number plates through photos by parking attendants as authenticator. The system is built from several devices, namely ultrasonic sensors to detect the presence of vehicles. Fingerprint sensor to detect fingerprints equipped with storage to store fingerprint templates. Webcam for taking photos of vehicles as verification when the vehicle exits the parking lot. While the portal door is driven by a servo motor. all systems are controlled using Raspberry Pi 3 using the python programming language. The test results on ultrasonic sensors are able to detect the presence of vehicles at a distance of 10-200 cm with an accuracy rate of 96%. Servo motor rotates position 0 ° if the Duty Cycle value is set 2.5 and rotates 90 ° if the DutyCycle 7.5 value. The webcam position is 2 meters from the location of the fingerprint sensor. The position of the pressed finger produces a faster process in identifying the character of the fingerprint during recording and matching fingerprints